Coughing in Small Animal Patients - Hsieh, Brisa M.; Beets, Alicia K. (Frontiers in Veterinary Science, 2020)
Cough is one of the most common complaints in human medicine. In veterinary medicine cough is equally frequent and plays a significant role in an owner's perception of their pet's quality of life. In human and veterinary medicine, therapy for chronic cough is often ineffective. The complexity of the cough pathway and species differences have made it difficult to develop an effective antitussive agent for veterinary patients. The few effective antitussive agents currently available are associated with significant adverse effects. Fortunately, several promising drugs currently being studied in human clinical trials may offer options for use of novel antitussive therapies in small animal patients. This article reviews current understanding about cough pathophysiology, diagnostic strategies used to uncover underlying etiology of cough, and examines available options for controlling cough, including novel antitussive therapies used in human medicine.